Phytochemical and cytotoxic investigations of the heartwood of caesalpinia sappan linn - Chuleeporn Ngernnak (2018)
© 2018 The Authors. Objective: The purpose of this study was to identify the chemical constituents in the dichloromethane extract by gas chromatography–mass spectrometry (GC–MS) analysis and evaluate the cytotoxic effects on leukemia cells of isolated compounds from Caesalpinia sappan Linn. Methods: Dichloromethane extract obtained from the heartwood of C. sappan was investigated by GC–MS and column chromatography. Cytotoxic effects on leukemia cells of the isolated compounds were examined using MTT assay. Results: The GC–MS analysis of dichloromethane extract from C. sappan revealed the presence of 14 compounds. Linoleic acid and β-sitosterol were found to be the major compounds presenting in 14% and 13%, respectively. The separation of the dichloromethane extract led to the isolation of brazilin (1) as a major compound, together with lupeol (2), and a mixture of β-sitosterol (3), and stigmasterol (4). Their structures were elucidated based on spectroscopic methods. Brazilin (1) showed a cytotoxic effect on human acute myeloid leukemia cell (KG1) and human acute myeloid leukemia stem cell (KG1a) with inhibitory concentration at 50% growth (IC50) values of 13.30 ± 0.49 and 12.24 ± 1.08 µg/ml, respectively. Conclusion: Many groups of phytochemical compounds in the dichloromethane extract of C. sappan were detected by GC–MS analysis. Some of them have been reported to possess various biological activities. Moreover, brazilin (1) isolated compound from C. sappan shows cytotoxicity on leukemia cells, which could be a potential anticancer property.